2011
DOI: 10.1001/archgenpsychiatry.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Categories by Patterns of Known Risk Factors

Abstract: Most suicide decedents could be classified by patterns of risk factors. Furthermore, most classes revealed a need for more connected services across medical, mental health/substance abuse, and court/social service systems. Reducing fragmentation across these agencies and recruiting family, friend, and community support for individuals experiencing mental health problems and/or other stress might significantly reduce suicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
75
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 41 publications
12
75
0
5
Order By: Relevance
“…We found that suicide deaths predominantly occurred among males, age 18 to 65, who suffered from depression or another major mental illness. These demographic patterns are in keeping with the literature on suicide, 17,29,32 and their strong effect helps to explain why the identified clusters all overlap to some degree. Nevertheless, our study did identify 5 clinically Cluster 1 had the highest proportion of females and involves suicidal acts that may have been less well planned and more impulsive.…”
Section: Suicide Clusterssupporting
confidence: 84%
See 4 more Smart Citations
“…We found that suicide deaths predominantly occurred among males, age 18 to 65, who suffered from depression or another major mental illness. These demographic patterns are in keeping with the literature on suicide, 17,29,32 and their strong effect helps to explain why the identified clusters all overlap to some degree. Nevertheless, our study did identify 5 clinically Cluster 1 had the highest proportion of females and involves suicidal acts that may have been less well planned and more impulsive.…”
Section: Suicide Clusterssupporting
confidence: 84%
“…A similar study 16 analyzed 148 suicide deaths in Hong Kong and found 2 groups: one associated with psychotic disorders, psychiatric treatment, and acute stress, and one associated with financial problems, chronic stress, and no psychiatric illness. Most recently, Logan et al 17 examined US National Violent Death Reporting System data on 28 703 suicide deaths and identified 9 different suicide clusters that differed based on rates of mental illness, substance abuse, past suicide attempts, stressors, and acute alcohol intoxication. While this is the largest and most comprehensive study examining suicide clusters to date, it is unclear to what extent the results can be generalizable outside the United States, most strikingly because 50% of them occurred by firearms.…”
mentioning
confidence: 99%
See 3 more Smart Citations